2021
DOI: 10.1002/adma.202006435
|View full text |Cite
|
Sign up to set email alerts
|

Buried Interfaces in Halide Perovskite Photovoltaics

Abstract: Understanding the fundamental properties of buried interfaces in perovskite photovoltaics is of paramount importance to the enhancement of device efficiency and stability. Nevertheless, accessing buried interfaces poses a sizeable challenge because of their non‐exposed feature. Herein, the mystery of the buried interface in full device stacks is deciphered by combining advanced in situ spectroscopy techniques with a facile lift‐off strategy. By establishing the microstructure–property relations, the basic loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
293
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 298 publications
(299 citation statements)
references
References 33 publications
6
293
0
Order By: Relevance
“…Lift-Off Process: The lift-off process was in the same way as Zhu et al reported. [63] Firstly, the PTAA (30 mg mL -1 , in toluene) solution was spincoated onto the pre-cleaned ITO at 4000 rpm for 40 s and annealed at 100 °C for 15 min in a N 2 -filled glovebox. The PTAA layer in the lift-off process serves as a sacrificial layer.…”
Section: Methodsmentioning
confidence: 99%
“…Lift-Off Process: The lift-off process was in the same way as Zhu et al reported. [63] Firstly, the PTAA (30 mg mL -1 , in toluene) solution was spincoated onto the pre-cleaned ITO at 4000 rpm for 40 s and annealed at 100 °C for 15 min in a N 2 -filled glovebox. The PTAA layer in the lift-off process serves as a sacrificial layer.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure accuracy, a mask with an aperture area of 0.09 cm 2 was employed during the measuring process. [ 80,81 ] The data were collected by the IV testing system with software (IVS‐KA5000). The stabilized power output was measured at the maximum power output bias voltage.…”
Section: Methodsmentioning
confidence: 99%
“…[ 89 ] The microstructure can also influence phase transitions, [ 90 ] thus affecting the temperature‐dependence of the FET properties. An important note is that the microstructure at the surface might vary from that at the bottom interface with the substrate – evident for example by scanning electron microscopy (SEM) [ 91 ] – which leads to different performance of the same film in different FET device architectures.…”
Section: Physics Of Perovskite Fetsmentioning
confidence: 99%
“…Defect management in this case is far more complex, considering the buried nature of that interface and the difficulty to not only modify it, but also to characterize it. [ 91 ] One possible solution could be based on the integration of passivating agents onto the substrate, prior to the deposition of the perovskite layer. [ 251 ] Alternatively, guided vertical segregation of the passivating additive towards the substrate during deposition of the perovskite precursor solution may also result in a well passivated bottom interface.…”
Section: Challenges In Perovskite Fet Research and Insights From Perovskite Optoelectronics That Can Address Themmentioning
confidence: 99%